2018
DOI: 10.1002/jbm4.10032
|View full text |Cite
|
Sign up to set email alerts
|

Differential Adaptive Response of Growing Bones From Two Female Inbred Mouse Strains to Voluntary Cage‐Wheel Running

Abstract: The phenotypic response of bones differing in morphological, compositional, and mechanical traits to an increase in loading during growth is not well understood. We tested whether bones of two inbred mouse strains that assemble differing sets of traits to achieve mechanical homeostasis at adulthood would show divergent responses to voluntary cage‐wheel running. Female A/J and C57BL6/J (B6) 4‐week‐old mice were provided unrestricted access to a standard cage‐wheel for 4 weeks. A/J mice have narrow and highly mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 45 publications
4
7
0
Order By: Relevance
“…Notably, young C57BL/6 J (B6) mice that ran showed significantly ( p < 0.01) lower intercondylar notch shape indices, a larger ACL cross-sectional area, and differential angular changes in the posterior tibial slopes, when compared to mice that did not run. These biomechanically induced differences in pubescent knee development were in accordance with an earlier mouse study [ 29 ] that reported significant differences in femoral diaphysis shape and strength following pre-pubescent exercise.…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…Notably, young C57BL/6 J (B6) mice that ran showed significantly ( p < 0.01) lower intercondylar notch shape indices, a larger ACL cross-sectional area, and differential angular changes in the posterior tibial slopes, when compared to mice that did not run. These biomechanically induced differences in pubescent knee development were in accordance with an earlier mouse study [ 29 ] that reported significant differences in femoral diaphysis shape and strength following pre-pubescent exercise.…”
Section: Introductionsupporting
confidence: 91%
“…These risk factors include a smaller ACL cross-sectional area [ 15 , 26 ], a narrower intercondylar notch width/shape [ 24 , 33 ], and a steeper posterior tibial plateau slope [ 6 , 9 ]. Previously, it has been reported that in controlled animal studies whole bone and ACL size and strength can be positively influenced through both voluntary [ 29 , 30 ] and forced [ 11 , 20 , 25 , 35 ] endurance running. However, little is understood about how the knee in general, and the anatomical risk factors for an ACL injury specifically, are impacted by increased physical activity throughout musculoskeletal growth.…”
Section: Introductionmentioning
confidence: 99%
“…Besides enhanced mechanical stimuli (muscular tension and axial loading) also systemic changes, that is, an increase in free testosterone levels, 17‐β‐estradiol, human growth hormone (hGH), insulin‐like growth factor 1 (IGF‐1), parathyroid hormone (PTH), calcitriol contribute to skeleton strengthening under exercise (Kemmler & von Stangel, 2019). Interestingly, voluntary wheel running, also applied in our study, has previously been shown to improve bone status in rodents (e.g., bone thickness, architecture and mineral content) both in physiological (Schlecht et al, 2018) and in different pathological conditions, for example, diabetes mellitus (Minematsu et al, 2017) and ovariectomy‐induced osteoporosis (Fonseca et al, 2011).…”
Section: Introductionsupporting
confidence: 53%
“…The difference in the ACL‐complex between B6‐control and exercise mice was also unexpected since previously we reported that B6 female mice that ran for 4 weeks during growth showed significantly narrower femoral and humeral diaphyses compared with controls . Instead, B6‐exercise mice showed no difference in the femoral side of the knee joint compared with their controls.…”
Section: Discussionmentioning
confidence: 84%
“…Previously, we reported a significantly larger bone mass in the femoral ( p = 0.01) and humeral ( p = 0.02) diaphyses and distal femora ( p = 0.02) following voluntary exercise between 8‐week‐old A/J females compared with their controls. This morphological change was not observed in their exercised B6 counterparts . Based on these outcomes, we also hypothesized that the gracile knee of A/J mice would show a greater expansion of the intercondylar notch, ACL, and CF within the femoral and tibial ACL entheses at 10 weeks of age following exercise when compared with exercised B6 mice.…”
mentioning
confidence: 92%